Nutrient Enrichment Mediates the Relationships of Soil Microbial Respiration with Climatic Factors in an Alpine Meadow - Zong, Ning (ScientificWorldJournal, 2015)
Quantifying the effects of nutrient additions on soil microbial respiration (R (m)) and its contribution to soil respiration (R (s)) are of great importance for accurate assessment ecosystem carbon (C) flux. Nitrogen (N) addition either alone (coded as LN and HN) or in combination with phosphorus (P) (coded as LN + P and HN + P) were manipulated in a semiarid alpine meadow on the Tibetan Plateau since 2008. Either LN or HN did not affect R (m), while LN + P enhanced R (m) during peak growing periods, but HN + P did not affect R (m). Nutrient addition also significantly affected R (m)/R (s), and the correlations of R (m)/R (s) with climatic factors varied with years. Soil water content (Sw) was the main factor controlling the variations of R (m)/R (s). During the years with large rainfall variations, R (m)/R (s) was negatively correlated with Sw, while, in years with even rainfall, R (m)/R (s) was positively correlated with Sw. Meanwhile, in N + P treatments the controlling effects of climatic factors on R (m)/R (s) were more significant than those in CK. Our results indicate that the sensitivity of soil microbes to climatic factors is regulated by nutrient enrichment. The divergent effects of Sw on R (m)/R (s) suggest that precipitation distribution patterns are key factors controlling soil microbial activities and ecosystem C fluxes in semiarid alpine meadow ecosystems.